Raw materials and functional designs of Fishtail projectile points from southern Brazil - Carbonera, Mirian; Loponte, Daniel (Journal of Lithic Studies, 2021)
This study analyses the lithic landscape and the selection of rocks used to manufacture Fishtail points (FP) in southern Brazil, their designs, and some functional aspects. In order to identify the offer of lithic resources, we carried out several surveys throughout 15 months in 47 counties in the Southern Brazil covered by the Botucatú - Serra Geral Vulcano Sedimentary Complex. The lithic composition of numerous hill slopes, fallen rocks, and accumulations of pebbles and boulders in the riversides was evaluated. The results show that basalts (including a small proportion of andesites and rhyodacites-rhyolites), and silicified sandstones, are ubiquitous in the landscape. Conversely, non-translucent cherts are scarce, so their acquisition would have been time-consuming. However, these local cherts were the rocks mostly used to manufacture these points, being another example of the selectivity for high quality rocks by Paleoamerican hunter-gatherers. The same cherts selected in southern Brazil to produce the FP were used to manufacture other point-types by local hunter-gatherers of the early and middle Holocene grouped in the so-called “Umbú Tradition”. Not a single FP of the entire collection analyzed here was made from silicified limestones, which is one of the most common raw materials among the Uruguayan FPs, nor were they made from quartzites as were most of the FPs of the Pampean plains. Regarding to the designs of these projectiles, some morphotypes appear to have been designed to produce multiple injuries through successive thrusts and withdrawals in the bodies of the prey, while in others, the design seems to have favoured penetration and fixation on the prey, suggesting in this case, a single shot technique for each projectile. As the maintenance process unfolded, especially for points below ~ 80 mm in length, they show features that negatively impacted their efficiency, including distinct asymmetries, somewhat open front angles, a decrease in the cutting perimeter and cross-sectional area, an increase in the bevel angle of the blade edges, and a tendency to a conical cross-section. Behaviours intended to counteract these problems were maximizing the length of the leading edge, maintaining the symmetry and the triangular blade resting on straight shoulders, and maintaining the aerodynamic properties as much as it were possible, in order to improve their lethality and the fixation capacity. Beyond these rejuvenation processes, three different morphotypes of points appear to be included within the sample. The first includes points over 120 mm and ~ 80 g in weight, with triangular or slightly lanceolate limbs, which mostly present straight shoulders, but there are also examples of rounded shoulders. The second design corresponds to projectiles between 110 and 87 mm and ~30 g in weight, with triangular or slightly lanceolate blades and straight shoulders. The third design presents the classic shape of these projectiles, with a fish silhouette, with maximum lengths below 90 mm, with a more robust and conceptually different design, where the angles of the edges of the blades and of the shoulders are equal, perhaps with the intention to facilitate the spear withdrawal to produce multiple injuries.